New public management(NPM)reform : A case of contracting out waste disposal - Abdul Mutalib, Rozita (2016)
Most of the reform in the public sector in Malaysia can be traced to thc influence of'NPM.NPM is a sign of a significant change in thc public sector management perspective. It is a global scientific in the 20th century in connection with the mechanism of governance in public service.All of the reforms and innovation are essential for creating a public service that is efficient and effective.